PERILAKU MASYARAKAT TERHADAP KEBERADAAN CSR PT PERTAMINA (PERSERO) DPPU NGURAH RAI DI DESA SIBANG KAJA, KECAMATAN ABIANSEMAL, KABUPATEN BADUNG - DANANJAYA, I. G. A. N.; SUARTA, I. G. (Majalah Ilmiah Peternakan, 2023)
The Jalak Bali is a species endemic to the island of Bali. One of PT Pertamina (Persero) Ngurah Rai’s CSR pro- grams is the conservation and breeding of Jalak Bali bird. The purpose of this study was to find out and analyze community behavior towards the existence of PT Pertamina (Persero) Ngurah Rai’s CSR, in Sibang Kaja village, Abiansemal district, Badung regency. The selection of this research location used a purposive method. The po- pulation in this study amounted to 235 families while the probability sample purposive technique used the slovin formula. So that the number of samples taken was 73 people. Data analysis in this study used descriptive analysis and Chi Square. Based on the results of research on community behavior towards the existence of PT Pertamina (Persero) DPPU Ngurah Rai’s CSR in Sibang Kaja village, it can be seen from the attitude of the community that they are in the agree category, while the level of knowledge and skills is in the high category. The results of the Chi Square analysis show that there is a real relationship between attitudes and knowledge from the calculated X2 value (18.21) > X2 (0.05) = 3.841. When viewed from the relationship between attitudes and skills from the calculated X2 value (13.18) > X2 (0.05) = 3.841 there is a real relationship. As well as the relationship between knowledge and skills with a calculated X2 value (7.08) > X2 (0.05) = 3.841 there is also a real relationship.